The rationale for using Periplaneta americana as a monarch drug of TCM in the treatment of damp-heat ulcerative colitis. (2021) - Lu, Ang; Tao, Lei; Li, Qi-Yan; Zhang, Jing-Na; Tang, Miao; Yu, Wan-Xin; Wang, Yu-Jia; Ai, Zhi-Qiong; Zhao, Yu; Liu, Heng; Wu, Xiu-Mei
Abstract: The aim of this research was to quantitatively and comprehensively explore the therapeutic effects and mechanism of action of traditional Chinese medicine (TCM) formulas, using Periplaneta americana as a monarch drug, against damp-heat ulcerative colitis (UC) in rats, by the application of multivariate statistical analysis. A high-sugar and high-fat diet was fed to Sprague Dawley (SD) male rats to develop the damp-heat physique. Trinitrobenzene sulfonic acid (TNBS) was then used on the damp-heat rats to induce UC. P. americana (P), Taraxacum mongolicum (T), and Poria cocos (F) have been in combination or individually adopted as ingredients in different TCM pharmaceutics to attenuate damp-heat physiques and/or to treat UC, because P. americana could promote blood circulation, nourish yin, and promote tissue regeneration, T. mongolicum has the effects on clearing heat and toxic materials, reduce swelling, and diuresis, while P. cocos possesses the function of clearing damp and promoting diuresis. Since these natural ingredients of TCM demonstrated overlapped effects against damp-heat UC, it calls the need to further illustrate the therapeutic effect and mechanism of action of P. americana as the monarch drug by comparing the effects of formulas of PT, PF, TF, and PTF. Each formula was administered by gastric lavage to four groups of randomly assigned laboratory animals for 14 consecutive days, while normal saline was given to the normal control and model control groups respectively. The damp-heat and UC indices, bio-marker levels in serum, and colonic mucosa were measured periodically, or the day after the last administration. The results of canonical correlation analysis and repeated-measures analysis of variance suggested that the therapeutic effects of formulas containing P. americana and T. mongolicum were better than those of the other formulas. The results of correspondence analysis suggested that the curative effects against damp-heat UC might be activated by reducing the expression of Interleukin-2 (IL-2) and increasing the level of transforming growth factor-beta (TGF- β ). The organically combined use of multiple multivariate statistical methods allowed comprehensive evaluation of the therapeutic effects of TCM formulas against chronic diseases with complex pathogenic factors. Graphical abstract: Image 1 Highlights: The DAI score could be used as the overall index to evaluate the curative effect for damp-heat UC in rats. Damp-heat UC might be regulated by reducing the expression of IL-2 and increasing the level of TGF- β. Combinatory use of multiple multivariate statistics allowed comprehensive evaluation of TCM formulas against damp-heat UC.